Pemrograman Sensor Coin Acceptor Pada Pengembangan Coffe Vending Machine Berbasis Internet Of Things (IoT) - Nisa Rara; Heri Suroyo (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
This research produces a prototype model of a coffee vending machine (CVM). The sensor used in the development of this machine is a multi-coin acceptor sensor. To drain the liquid from the tank to the coffee cup, a mini electric pump is used which is programmed through a relay connected to the digital pin of the Arduino microcontroller. In microcontroller programming, the Internet of Things (IoT) based multi coin acceptor sensor uses the C language which is uploaded to the Arduino Uno Microcontroller. This research uses R & D (Research and Development) methods. The development of IoT-based CVM used the Prototype method. The multi coin acceptor sensor is used to detect currency coins. This sensor has 3 speed levels in detecting coins, namely medium, slow and fast. In this study also obtained the results of testing the accuracy of the multi coin acceptor sensor as follows: 1) This sensor has an average 97.7% success rate for all types of coins tested. 2) The accuracy of the multi coin acceptor sensor is highest in the medium setting with a 99.2% success rate, while the slow and fast settings have an accuracy rate of 96.8% success. From testing in the program, it is also found that the speed of a mini electric pump to fill a 200 ml glass requires a delay time of 6000 ms.